PERSPEKTIF PENGELOLAAN WILAYAH KEPULAUAN ERA OTONOMI DAERAH - S.Sos, MM, Abdul Muis (Pusat Pelatihan dan Pengambangan dan Kajian Desentralisasi dan Otonomi Daerah Lembaga Administrasi Negara, 2010)
Future local conception in maritime management relates to the oceanic position and function of sea as a mean to unify autonomous region and administrative area in implementation of genuine and responsible local autonomy policy. Hence, with the absence of adequate regulation on unifying authority in vast maritime archipelago, disparity in marine resource management and exploitation would be inevitable.